A Study of the Effect of Conservatism on Stock Return: Evidence of Iranian Chemical Industry - Salehi, Mahdi; Zareijam, Azam (Journal of Asian Business Strategy, 2011)
Financial statements are the main part of financial reporting process. Purpose of financial statements is providing classified information about the financial situation, financial performance, and financial flexibility for the business unit that can be useful in a wide range of users of financial statements used in economic decision. The purpose of financial reporting and accounting principles, will require information that may be provided by financial reporting, be enjoyed of certain features. Based on theoretical concepts of financial reporting, the information can be useful that is qualitative feature of financial information. The main qualitative characteristics associated with information content are relevancy and reliability, and conservative or precaution is one of the main characteristics of reliability. Conservative has been interpreted as accountants tend to require a higher degree of quality to identify the good news confirmed as profit and to identify the bad news as losses. The aim of the current study is assesses the relationship between conservatism and share return of chemical companies listed on Tehran Stock Exchange. Statistical Society is pharmaceutical and chemical companies during 2004-2010. Required data in this study has been collected using the library method. Other word, information has been gathered from existing documents and databases of Tehran Stock Exchange. The Study method is solidarity. Information required by companies manage database processor is gathered and then summarized and calculations required in Excel spreadsheet for analysis is prepared.